PROMOTING GLOBAL CITIZENSHIP THROUGH ENGLISH: THE ROLE OF CULTURAL AWARENESS AND LITERATURE IN LANGUAGE LEARNING - Bobojonov Qobiljon Abdurahim o‘g‘li (ZAMONAVIY TILSHUNOSLIK ISTIQBOLLARI: MUAMMOLAR VA YUTUQLAR MAVZUSIDA XALQARO ILMIY AMALIY ANJUMAN, 2025)
This article discovers the role of English as a global lingua franca and emphasizes the significance of implementing cultural awareness into English language teaching. It emphasizes how learning English promotes intercultural competence, empathy, and global engagement. The article also provides practical classroom strategies for building a culturally inclusive atmosphere to foster tolerance and comprehension among students.